A decoupled controller design approach for formation control of autonomous underwater vehicles with time delays. Issue 15 (1st October 2013) - Yang, Huizhen; Wang, Chuanfeng; Zhang, Fumin
Abstract : Formation control for a group of autonomous underwater vehicles (AUVs) is challenging due to the complex systems dynamics and time delay in the cooperative feedback loops. This paper introduces a decoupled design procedure, so that formation controllers designed for particle dynamics can be generalised to formation controllers for fully actuated AUVs with six‐degree‐of‐freedom dynamic models for motions in three‐dimensional space. The orientation control and the translation control are first decoupled following a standard inner–outer loop approach. Then, a geometric approach is followed to separate the translation dynamics into formation shape dynamics and formation centre dynamics. Coupling terms between the two portions of the dynamics are treated as perturbations and are tolerated by a robust formation‐keeping controller. The controller is also robust to constant bounded time delays. This decoupling procedure simplified the entire design process comparing with other existing approaches with similar goals. Both rigorous theoretical analysis and simulation results are presented to justify the effectiveness of this method.